Experimental and theoretical insights into spectroscopy and electrochemistry of Re(I) carbonyl with oxazoline-based ligand. (1st October 2019) - Świtlicka, Anna; Choroba, Katarzyna; Szlapa-Kula, Agata; Machura, Barbara; Erfurt, Karol
Graphical abstract: A novel rhenium(I) carbonyl complex with oxazoline-based ligand – X-ray studies and spectroscopic and electrochemical properties. Abstract: Structural, spectroscopic and electrochemical properties of a novel rhenium(I) carbonyl complex with oxazoline-based ligand, 2-(4, 5-dihydro-2-oxazolyl)quinoline ( quinox ), are discussed herein. The molecular formula of the title compound fac –[ReCl(CO)3 (quinox)] was determined by X-ray analysis and confirmed spectroscopically using IR and NMR spectroscopy, including multidimensional techniques 1 H– 13 C HMBC, 1 H– 13 C HMQC, 1 H– 1 H COSY. The electrochemical behaviour of1 and the free ligand was investigated using cyclic voltammetry (CV) and differential pulse voltammetry (DPV). The ground and excited state properties of1 and quinox were investigated utilizing absorption and emission spectroscopy, with photoluminescence studies performed both in solution and solid state. The electronic structure of the Re(I) complex was further investigated theoretically at DFT/PBE1PBE/DEF2-TZVPD/6-31+G(d, p) level.